2015
DOI: 10.1515/sgem-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Scale Effect in Direct Shear Tests on Recycled Concrete Aggregate

Abstract: Abstract:The depletion of natural resources is forcing researchers to explore the possibilities of new aggregates, such as recycled concrete aggregate (RCA). In this article, the mechanical properties and the influence of the size of the direct shear box on the obtained parameters were examined. The study was conducted in two apparatus: medium (120 × 120 mm) and large (250 × 250 mm). In each of these devices, a total of 6 tests were performed: 3 for dry sample and 3 at optimum moisture content. From the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
2
3
0
1
Order By: Relevance
“…The maximu max) was equal to 1.94 g/cm 3 and was achieved at the optimum moisture about 9.5%. Very similar results to those are presented here, but for the b 0.05 to 2 mm can be found in Soból et al [33]. Based on the results of com be concluded that the tested RCA is compacted in a similar way to na where a characteristic value of the optimum moisture content is observe non of the strong linkage between wopt with ρd, max, and with the narrow content noticeable in this study is a determinant of coarse-grained soils centage of fine particles content.…”
Section: Physical Properties Resultssupporting
confidence: 92%
“…The maximu max) was equal to 1.94 g/cm 3 and was achieved at the optimum moisture about 9.5%. Very similar results to those are presented here, but for the b 0.05 to 2 mm can be found in Soból et al [33]. Based on the results of com be concluded that the tested RCA is compacted in a similar way to na where a characteristic value of the optimum moisture content is observe non of the strong linkage between wopt with ρd, max, and with the narrow content noticeable in this study is a determinant of coarse-grained soils centage of fine particles content.…”
Section: Physical Properties Resultssupporting
confidence: 92%
“…First, the internal friction angles of the soils were determined according to ASTM D3080 [26] with the traditional direct shear test method, but using a different-sized shear box (100 x 100 x 40 mm 3 ) [27][28][29][30]. The friction angle of the soil -GM interfaces was determined according to ASTM D5321 [31] using a direct shear apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…The resilient modulus representing the behavior of pavement layers under repeated traffic loads, which is primarily used for determining the structural thickness of the road and evaluating the performance of this structure, was investigated and compared with the results of other studies 66 69 . It has also been shown in previous studies that the MR of all samples varies with the total stress as a result of resilient modulus tests; and as has been shown in this study, it is almost linear to the and the MR values 70 , 71 .…”
Section: Experimental Studymentioning
confidence: 99%